THE IMPLEMENTATION OF THINK PAIR SHARE TYPE IN LEARNING COMPILATION MATERIAL TO IMPROVE STUDENTS' COOPERATION - Annisa Puspitarini; Widayati Widayati (Universitas Ahmad Dahlan, 2019)
Students' cooperation is still low. Students prefer to work individually in the learning process. The objective of this research is to improve students' corporation by implementing corporative style 'Think Pair Share' Class VII at Islamic Junior High School (MTS) Muhammadiyah KarangkajenÂ First Semester in Academic Year 2017/2018 This is a classroom action research in which took Students' Class VII A at MTS Muhammadiyah Karangkajen as the object to implement cooperative learning style Think Pair share in learning mathematic. This research was conducted in two cycles, and each cycle had two meetings. The data collecting technique used observation and interview. The Data was analyzed by using qualitative and quantitative descriptive analysis. This research showed that cooperative learning style 'Think Pair Share' could improve the students' cooperation in Class VII A at MTs Muhammadiyah Karangkajen First Semester in Academic Year 2017/2018. It is proved in the result of observation in each cycle. The first cycle showed 42% (Average), and the second cycle increased to be 74% (High). Moreover, students' interviewing showed students' cooperative improvement from the first cycle to the second cycle.